Comparative study for three different structures of the p-n junction on Silicon (111) wafer. / Amirul Aiman Ahmad Hisham - Ahmad Hisham, Amirul Aiman (2011)
This project is about a comparative study for 3 different structures of the p-n junction on Silicon (111) wafer. A study about p-n junction was important since it serves as a basis on understanding other semiconductor devices that play a major role on modern technology development nowadays. P-N junction was actually formed by locating the p-type and n-type semiconductors together. And to achieve this, a process called doping was used. Doping is a process which introduces impurities into an intrinsic semiconductor to change its electrical characteristic either by ion implantation, diffusion of dopant, or epitaxy techniques. But in this project, it would be only concentrated on diffusion of dopant since it is the most convenient way. While for the locating the p-type and n-type semiconductors together, there were actually several possible arrangements or structures of locating the p-type and n-type. Based on that idea, this project will investigates the electrical characteristics of each type of the three structures that had been planned to fabricated, the differences, and most ideal structure to fabricate a p-n junction. Method that will be used in fabricating the p-n junction is the same as the basic method in fabricating a p-n junction process except for the lithography process since there will be three different structures of the p-n junction that will be going to be fabricated. Thus the mask used will be different from each structure. And as for the result, it will be obtained by current-voltage (I-V) measurement. From that data, electrical characteristic for each structure, the differences and the most ideal design structures for making a p-n junction can be concluded. After the project had been completed, it shows that structure 3 with large dimension (sample 6) was the best structure for p-n junction fabrication.